Oversized versus Non-oversized Prosthesis: Midterm Outcomes after Transcatheter Aortic Valve Replacement Using SAPIEN 3 Valve - Useini, Dritan; Beluli, Blerta; Christ, Hildegard; Mügge, Andreas; Patsalis, Polykarpos; Schlömicher, Markus; Haldenwang, Peter; Bechtel, Matthias; Strauch, Justus (The Thoracic and Cardiovascular Surgeon, 2020)
Background A certain degree of prosthesis oversizing is recommended for the SAPIEN 3 (S3; Edwards Lifesciences Corp., Irvine, California, United States) to ensure device success. We aimed to investigate midterm outcomes in patients who received oversized (OS) S3 valve after transapical–transcatheter aortic valve replacement (TA-TAVR).Methods Out of 122 patients with aortic stenosis who underwent TA-TAVR using S3 at our institution, 42 received OS prosthesis. We used computed tomography (CT) derived effective diameter to assess oversizing. We defined oversizing if the labeled diameter of the selected valve for implantation was ≥2 mm bigger than the effective annulus diameter calculated by the annulus area. We conducted a midterm follow-up and compared the OS cohort with the non-OS (nOS) cohort.Results The study groups showed similar risk score and age (STS [Society of Thoracic Surgery] score: 5.4 ± 3; mean age: 80.7 ± 5.7). The 30-day mortality was 7.1% in OS versus 2.4% in nOS. The 30-day all-stroke was 2.4% in OS versus 0% in nOS. The 1- and 3-year all-cause mortality were 28.5 and 42.8% in OS versus 21.9 and 26.8% in nOS, respectively. Midterm freedom from death and from cardiocerebral events was similar in both groups. Moderate/severe paravalvular leakage occurred in 0% in OS versus 5.4% in nOS. The postdilation rate was 7.1% in OS versus 15.3% in nOS. The rate of new permanent pacemaker implantation (PPI) was 15.7% in OS versus 9.3% in nOS. The STS score was detected as an independent predictor of mortality.Conclusion Oversizing reduces the risk of device failure and intraprocedural postdilation but increases the risk of PPI. Early and midterm morbidity and mortality after OS and nOS with S3 are comparable.
Keywords: heart valve; transapical; aortic valve; outcomes